1+(8x-5)=(6x+6)

Simple and best practice solution for 1+(8x-5)=(6x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+(8x-5)=(6x+6) equation:


Simplifying
1 + (8x + -5) = (6x + 6)

Reorder the terms:
1 + (-5 + 8x) = (6x + 6)

Remove parenthesis around (-5 + 8x)
1 + -5 + 8x = (6x + 6)

Combine like terms: 1 + -5 = -4
-4 + 8x = (6x + 6)

Reorder the terms:
-4 + 8x = (6 + 6x)

Remove parenthesis around (6 + 6x)
-4 + 8x = 6 + 6x

Solving
-4 + 8x = 6 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-4 + 8x + -6x = 6 + 6x + -6x

Combine like terms: 8x + -6x = 2x
-4 + 2x = 6 + 6x + -6x

Combine like terms: 6x + -6x = 0
-4 + 2x = 6 + 0
-4 + 2x = 6

Add '4' to each side of the equation.
-4 + 4 + 2x = 6 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = 6 + 4
2x = 6 + 4

Combine like terms: 6 + 4 = 10
2x = 10

Divide each side by '2'.
x = 5

Simplifying
x = 5

See similar equations:

| -8-5(7-2v)=-113 | | 4x-20x=-24 | | 0.4(5x+35)=2.0(x+7) | | (4x+5)+(2x^3+3x-4)+(-x^2-2x+1)= | | (-x+8y)(-x-8y)= | | (5x-4)-2=2x | | -2(2p+2)-2(1-p)=3(3p+2)-3 | | 1005=5x+950 | | x-3+5=2x | | 8=7x-1 | | (2x^2+3x-5)+(-3x^2-4x+4)= | | (-2x+3)(-2x-3)= | | 3a+9=4a-11 | | 14.4*13= | | 16x^4+54x= | | 6x^2+5x+15=2x^2-3x+12 | | 17x+173x-17=19(10x+14) | | 18x+15-(5x)=41 | | 7m+6m+7=3m-3 | | 22a+23-20a=29 | | 8x^2+2x+27=0 | | (5x^3+6)+(x^3+3x+4)+(2x^2-3x-10)= | | 8x+32x-5=10(4x+8) | | 4x-3x=4x+5 | | (110c^3)(-c^9)= | | -2+3=5x-21 | | -7=2+19 | | 4cos(x)=5sin(x) | | 3x(x+2)=-3x(x+1)+4x+4 | | sqrt(6x+30)+7=x | | 225x-4x-4= | | x+20=2x-5 |

Equations solver categories